Islamic Ecotheology as the Foundation of Environmental Ethics: Reinterpreting Fiqh al-Bi'ah in the Contemporary Ecological Crisis - Musyaari Rasyid; M. Riyad Auni; Afifa Nurfitria Wadina (Mir'ah: Family Law and Legal Culture, 2025)
The global environmental crisis requires solutions that go beyond purely technical approaches. This study examines Islamic ecotheology and the reinterpretation of fiqh al-bi'ah as a normative foundation for fostering ecological awareness among the Muslim community. Employing a qualitative library research approach and thematic analysis of primary sources from the Qur'an, hadith, and contemporary literature, the findings reveal that the concepts of khalīfah (stewardship), amānah (trust), maqāṣid al-sharī'ah, tawāzun (balance), and the prohibition of fasād (environmental destruction) constitute the core principles of Islamic environmental ethics, emphasizing humanity's responsibility to preserve nature. The reinterpretation of fiqh al-bi'ah demonstrates strong potential as a practical moral and legal framework for encouraging behavioral change toward just and sustainable environmental management, particularly within the Indonesian context. The main contribution of this study lies in developing a conceptual framework that integrates Islamic ecotheology with the reinterpretation of fiqh al-bi'ah, thereby enriching contemporary Islamic environmental ethics and providing a contextual foundation for addressing current ecological challenges. The findings also contribute to strengthening ecology-based Islamic education and culturally responsive environmental policy development. Nevertheless, this study is limited to library research and does not empirically examine the implementation of the proposed framework within Muslim communities or Islamic educational institutions. Future studies are therefore recommended to conduct empirical investigations to assess the effectiveness of fiqh al-bi'ah in promoting ecological awareness and sustainable environmental behavior.